Disclosure das provisões: a relação entre as obrigações de prazos ou valores incertos e os ratings corporativos - Santos, Henrique Soares de Souza (2021)
Accounting for corporate obligations in view of the possibility of future events allows flexibility for accountants. This flexibility, arising from the subjectivity of accounting standards, involves risks measured by criteria determined by the entity regarding operational and financial aspects. The obligations under uncertainty of terms or amounts, recognized in the statements include part of these aspects that might impact the future ability to honor corporate commitments. The main objective of this research is to verify the relationship between the recognition of the provision values and Standard & Poor's credit rating assigned to non-financial traded companies, with shares in Brazil, Bolsa, Bacão in the period from 2010 to 2019. Hence expanding the understanding of the relevance of provisions, empirical evidence of the moderating role of recognition in accounting accounts. The analysis was based on the theoretical basis of the Disclosure Theory, especially with regard to changes in accounting standards introduced in 2010, with CPC 25, based on IFRS, as a mechanism for transparency and quality of information of obligations under uncertainty of terms or amounts that may affect the performance indicators, social and environmental reputation of the firms. In order to achieve the objective of research, a multinomial logistic regression was set by using as dependent variable the credit rating of the companies and other independent variables evidenced by the literature and addition of the variable “provisioned liquidity”. Among the main results in the modeling it was found that the provisions have more influence on the results of the categories of lower quality classifications in the evaluated sample of Brazilian companies. It was possible to verify an increase in the values of provisions in the balance sheets of firms that recognize the accounting element over the 10 years of the validity of the standard. It may be due to the learning process for the application of IFRS, as well as the increase in the environmental exploration and the litigations in which the companies have been sued, although still focused on long-term accounts, without proper allocation between accounts by distinguishing the types of values. As contributions of the research, it is noteworthy that, despite the need for improvements in the disclosure and recognition of provisions, there is evidence that a traditional CRA may use provision amounts as a determinant of credit quality, which may suggest that these are considered in the analysis of creditors in Brazil.